Pengaruh Locus of Control dan Ketidakpastian Tugas pada Hubungan Antara Partisipasi Anggaran dan Kepuasan Kerja Manajemen Perguruan Tinggi Muhammadiyah se-Indonesia - Adam, Helmy (TEMA, 2006)
This research aimed to find the caused of the inconsistencies research finding of the role of locus of control as moderating variable on the relationship between budgetary participation and job satisfaction, which happened on Brownell (1981, 1982a), Frucot & Shearon (1991), and Indriantoro (1995). Lucket & Eggleton’s (1991) study, indicate that task uncertainty could determine the effect of locus of control as a moderating variable. This research used 88 Dean/Financial Dean Assistant on the Higher Education of Muhammadiyah in Indonesia. Using 3-way interaction, indicate that task uncertainty had significant effect on the locus of control’s moderating role. In the higher task uncertainty conditions, managers who had internal locus of control, will more satisfied when given higher participation, and managers who had external locus of control, will more dissatisfied when given higher participation. In contrast, in the lower task uncertainty, locus of control didn’t have moderating roles, because both internal and external had the same effect (positive) on responding the budgetary participation increasing. Keywords: Budgetary Participation, Locus of Control, Task Uncertainty, 3-way Interaction